Assessment of sublethal ecotoxicity of solvents on larvae of a model native amphibian (Lithobates pipiens) - Young, Sarah D.; Gavel, Melody J.; Gutierrez‐Villagomez, Juan M.; Forbes, Mark R.; Robinson, Stacey A. (Journal of applied toxicology, 2020)
Carrier solvents are used frequently in toxicity testing to assist hydrophobic chemicals into solution, but such solvents may have toxic effects on test subjects. Amphibians are model organisms in toxicity studies; however, little is known about the direct effects of solvents on native amphibians. Following modifications to standardized guidelines for native species, we used acute 96‐hour exposures to assess the direct effects of three common solvents on survival, differences in morphology and occurrence of abnormalities of northern leopard frog larvae (Lithobates pipiens). The solvents, dimethyl sulfoxide (DMSO), ethanol (ETOH) and acetone (ACE) were used at nominal concentrations ranging from 1 to 100 μL/L. We also conducted a 30‐day exposure to assess the direct chronic effects of DMSO at 1 and 5 μL/L, on larval growth, development and sex differentiation, but found no effects. Acute exposure to solvents also had no effect on the survival of larvae, but we found significant abnormalities in tadpoles acutely exposed to 100 μL/L ACE. Acute exposure to DMSO and ETOH had further concentration‐dependent effects on larval morphological traits. Our study suggests that DMSO and ETOH at ≤20 μL/L may be used as solvents in amphibian ecotoxicological studies, but ACE should be limited to ≤50 μL/L in ecotoxicity studies and perhaps much less (≤10 μL/L) in studies with other amphibians, based on a review of existing literature. We emphasize pilot studies when using solvents on acute and chronic ecotoxicity tests, using native amphibians. Carrier solvents are commonly used to assist chemicals into solution; however, little is known about their potential toxic effects on amphibians. As amphibians are model organisms in ecotoxicity testing, we assess the effects of three common carrier solvents, dimethyl sulfoxide, ethanol and acetone, on larvae of northern leopard frogs (Lithobates pipiens). Acute exposure to solvents affected differences in morphology and presence of abnormalities. Our results emphasize the importance of undertaking pilot studies when using solvents in native amphibian ecotoxicity tests.